2006
DOI: 10.1002/jbm.a.30740
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal application of chitosan and UV‐cross‐linkable chitosan

Abstract: The suitability of chitosan and UV-cross-linkable chitosan for intraperitoneal use, for example as a barrier device for preventing peritoneal adhesions or for drug delivery, was examined. In vitro experiments using two major cell types present in the peritoneal cavity (mesothelial cells and peritoneal macrophages) revealed neither attractive interactions between cross-linked chitosan gels and the cells nor a proliferative effect. However, the same UV-cross-linked chitosan applied in the peritoneal cavity of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 28 publications
3
58
0
Order By: Relevance
“…Chitosan-One initial approach was to use a UV cross-linkable chitosan hydrogel [55], based on the view that chitosan was generally considered to be biocompatible [56,57]. We demonstrated in vitro that it had excellent properties in terms of cohesiveness and macromolecule release kinetics (data not shown).…”
Section: 21mentioning
confidence: 94%
“…Chitosan-One initial approach was to use a UV cross-linkable chitosan hydrogel [55], based on the view that chitosan was generally considered to be biocompatible [56,57]. We demonstrated in vitro that it had excellent properties in terms of cohesiveness and macromolecule release kinetics (data not shown).…”
Section: 21mentioning
confidence: 94%
“…In addition, it is important to study the mechanisms by which biomaterials cause tissue injury. Often, the simple in vitro tests that are commonly used to assess cytotoxicity do not predict outcome in vivo (Yeo et al, 2006a). However, in vivo screening of biomaterials is expensive, tedious, and has the ethical problem of involving living creatures.…”
Section: Biocompatibility and Cytotoxicitymentioning
confidence: 99%
“…Of note, a material's apparent lack of cytotoxicity does not necessarily predict biocompatibility. For example, a cross-linked chitosan that was minimally toxic to mesothelial cells in vitro caused marked adhesions when placed in the peritoneum (11).…”
Section: Biomaterials For Tissue Engineeringmentioning
confidence: 99%
“…Direct action of putatively inert materials is seen in the following examples relating to carbohydrate-based matrices. In the crosslinked chitosan mentioned above that caused severe peritoneal adhesions, it was found that the material itself caused marked increases in the expression of MIP-2 (a murine IL-8 analogue) and tumor necrosis factor alpha (TNF-␣) in mesothelial cells (11). A cross-linked hyaluronic acid (35) used to prevent peritoneal adhesions (61) was shown to cause a small increase in tissue plasminogen activator in mesothelial cells, which might have contributed to the anti-adhesion efficacy.…”
Section: Biomaterials As Bioactive Agentsmentioning
confidence: 99%